Regioselective Photocyclization Reactions of 3‐Allyloxy‐6‐chloro‐2‐(thiophen‐3‐yl)‐4H‐chromen‐4‐one: Solvent Effect. (2nd April 2013) - Kamboj, Ramesh C.; Kumar, Dinesh; Arora, Rita; Berar, Surinder; Sharma, Geeta
Abstract : Abstract : The photo‐irradiation of thienylchromenone resulted in the regioselective cyclization which is exclusively controlled by the nature of solvent used as reaction medium. Compared to nonpolar medium, polar solvent furnished a diverse array of novel angular tetracyclic photoproducts with gem‐dihydro functionality and exocyclic double bonds on the fused pyran ring, which is unprecedented to best of our knowledge.